1998
DOI: 10.1002/(sici)1097-4636(19981215)42:4<549::aid-jbm10>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Moisture-dependent renaturation of collagen in phosphoric acid etched human dentin

Abstract: We used atomic force microscopy (AFM) to investigate the effects of acidic and aqueous treatments on human dentin. Two basic points were determined: the first is the ability of AFM to discriminate the effect of phosphoric acid (pH approximately equal to 1) on polished dentin, and the second is the demonstrable effect of moisture on fibrous collagen structure. AFM images confirmed that the polishing process led to the removal of both smear layer and smear plugs. Our AFM study of undried dentin, which was then a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 18 publications
(23 reference statements)
1
22
0
2
Order By: Relevance
“…On the sub-fibrillar level, TEM showed the extruded collagen fibres to be composed of fibrils with a degree of axial alignment that exhibited the characteristic D banding of fibrous collagens, which results from alternating overlap and gap zones, produced by the specific packing arrangement of the 300 nm long and 1.5 nm wide collagen molecules [2,[12][13][14][15][16][17]22,[45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]. The ability of type I collagen to form striated fibrils is believed to involve specific charge-charge and hydrophobic interactions.…”
Section: Structural Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the sub-fibrillar level, TEM showed the extruded collagen fibres to be composed of fibrils with a degree of axial alignment that exhibited the characteristic D banding of fibrous collagens, which results from alternating overlap and gap zones, produced by the specific packing arrangement of the 300 nm long and 1.5 nm wide collagen molecules [2,[12][13][14][15][16][17]22,[45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]. The ability of type I collagen to form striated fibrils is believed to involve specific charge-charge and hydrophobic interactions.…”
Section: Structural Characteristicsmentioning
confidence: 99%
“…Water molecules are known to form an integral part of the triple helix structure of the collagen molecule and in the assembly of collagen molecules into organized fibres. It has been shown that these structurally important water molecules are not removed during air-drying [57]. It has further been argued that rigidification of fibres is accomplished by the loss of water from the fibres, since the flexibility of concentrated liquid crystalline phases (such as a collagen fibre) is a very sensitive function of the volume fraction of solvent remaining in the fibre [52].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…3). A variety of acid types (citric acid [41], phosphoric acid [40] and [42], formic acid [43]) and concentrations have been used to etch the surface of mineralized tissues, with varying degrees of success. Chelating agents such as Ethylenediaminetetraacetic Acid (EDTA) have also been used successfully.…”
Section: Investigating Collagen In Bonementioning
confidence: 99%
“…The samples employed in these studies include regenerated collagen fibrils [8][9][10][11][12][13][14] and native fibrils obtained from the mammalian tendon [9,11,[15][16][17][18][19], cornea and sclera [20], and dentin [21]. Most of the studies were carried out using dehydrated fibrils in air under ambient condition.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies were carried out using dehydrated fibrils in air under ambient condition. The exception is the work by Baselt et al [9] and El Feninat et al [21], in which, respectively, bovine dermal collagen fibrils and the acid-etched dentin were studied partially in aqueous media. As already mentioned by Ushiki et al [3], in order to correlate the surface structure of a collagen fibril to the physiological properties, it is necessary to investigate their surfaces under a condition similar to the physiological environment.…”
Section: Introductionmentioning
confidence: 99%